2015
DOI: 10.7567/apex.8.095701
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial energy level alignments between low-band-gap polymer PTB7 and indium zinc oxide anode

Abstract: The interfacial energy level alignments between poly(thieno[3,4-b]-thiophene)-co-benzodithiophene (PTB7) and indium zinc oxide (IZO) were investigated. In situ ultraviolet photoemission spectroscopy measurements were conducted with the step-by-step deposition of PTB7 on IZO substrate. All spectral changes were analyzed between each deposition step, and interfacial energy level alignments were estimated. The hole barrier of standard ultraviolet-ozone treated IZO is 0.58 eV, which is lower than the value of 1.09… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The LUMO levels were calculated by considering the measured HOMO levels by UPS and the corresponding charge-transporting gaps (2.50 eV for P3HT, 2.25 eV for PTB7, and 2.20 eV for PCBM). 39,50 As a result, we obtained the E HOMO−D − E LUMO-A of P3HT:PCBM and PTB7:PCBM equal to 1.03 and 1.23 eV, respectively. The origin of the difference of electronic structure between P3HT:PCBM and PTB7:PCBM might be due to the difference in positive energy integer charge transfer state (E ICT+ ) of the two polymers.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…The LUMO levels were calculated by considering the measured HOMO levels by UPS and the corresponding charge-transporting gaps (2.50 eV for P3HT, 2.25 eV for PTB7, and 2.20 eV for PCBM). 39,50 As a result, we obtained the E HOMO−D − E LUMO-A of P3HT:PCBM and PTB7:PCBM equal to 1.03 and 1.23 eV, respectively. The origin of the difference of electronic structure between P3HT:PCBM and PTB7:PCBM might be due to the difference in positive energy integer charge transfer state (E ICT+ ) of the two polymers.…”
Section: Resultsmentioning
confidence: 82%
“…According to the XPS and UPS results, the energy level diagrams of P3HT:PCBM and PTB7:PCBM can be obtained as shown in Figure . The LUMO levels were calculated by considering the measured HOMO levels by UPS and the corresponding charge-transporting gaps (2.50 eV for P3HT, 2.25 eV for PTB7, and 2.20 eV for PCBM). , As a result, we obtained the E HOMO–D – E LUMO‑A of P3HT:PCBM and PTB7:PCBM equal to 1.03 and 1.23 eV, respectively. The origin of the difference of electronic structure between P3HT:PCBM and PTB7:PCBM might be due to the difference in positive energy integer charge transfer state ( E ICT+ ) of the two polymers. , The relatively small E ICT+ of P3HT has been reported with strong charge transfer to other materials in contact, which possibly facilitates the large energy level shifting .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, band bending was observed upon introducing P0 and P4 interlayers in films of ITO/PEDOT : PSS, [21,24] owing to the formation of interfacial dipoles with P0 and P4. [25][26][27] The work function of P0 and P4 is increased by the removal of hydrocarbons through ozone treatment at the interface with ITO, [25,26] and the sulfur group of P4 forms a higher dipole and induces a relatively larger band bending at P4 than at P0. [27] Therefore, the introduction of P4 can improve charge transport and suppress current injection in perovskite devices.…”
Section: Resultsmentioning
confidence: 99%
“…The energy level alignments at the interfaces of poly­(3-hexylthiophene-2,5-diyl) (P3HT)/CuSCN/indium tin oxide (ITO) were determined and compared with that of P3HT/ITO, which is a typical donor/anode system in OPVs. In situ deposition of a P3HT layer on CuSCN with a stepwise deposition-measurement sequence was conducted using vacuum electrospray deposition (VESD), which enabled incremental deposition of a polymer layer to probe its interfacial electronic structure. It was revealed that the highest occupied molecular orbital (HOMO) of P3HT is aligned with the band-tail states of CuSCN, and thus, barrier-less hole extraction between P3HT and CuSCN occurs. This hole barrier reduction was also confirmed with current density–voltage ( J – V ) measurements of hole-dominated devices.…”
mentioning
confidence: 99%